2021
DOI: 10.3389/fsurg.2021.682348
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lymphadenectomy on Outcomes of Early-Stage Ovarian Cancer: A Systematic Review and Meta-Analysis

Abstract: Objective: The study aimed to assess if additional lymphadenectomy with primary staging surgery improves overall survival (OS) and disease-free survival (DFS) of early-stage ovarian cancer (ESOC).Methods: PubMed and Embase databases were searched for any type of study comparing OS or DFS between lymphadenectomy and control groups for any type of ESOC. Adjusted hazard ratios (HR) were pooled in a random-effects model.Results: Twelve studies were included. Meta-analysis indicated that lymphadenectomy is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The objective of this video is to present a complete pelvic and para-aortic lymph node staging by retroperitoneal robotic-assisted laparoscopy of an earlystage epithelial ovarian cancer. 1 We present the case of a 38-year-old patient who was diagnosed with an infiltrative subtype mucinous ovarian cancer stage IA. Fertility sparing surgery was indicated provided there was no lymph node involvement.…”
Section: Gynecological Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this video is to present a complete pelvic and para-aortic lymph node staging by retroperitoneal robotic-assisted laparoscopy of an earlystage epithelial ovarian cancer. 1 We present the case of a 38-year-old patient who was diagnosed with an infiltrative subtype mucinous ovarian cancer stage IA. Fertility sparing surgery was indicated provided there was no lymph node involvement.…”
Section: Gynecological Cancermentioning
confidence: 99%
“…The objective of this video is to present a complete pelvic and para-aortic lymph node staging by retroperitoneal robotic-assisted laparoscopy of an early-stage epithelial ovarian cancer 1…”
mentioning
confidence: 99%
“…Lymphadenectomy in patients with early-stage EOC has been suggested to completely remove the occult tumor from the lymph node (therapeutic role) and define the disease stage, which influences the choice of systemic chemotherapy (diagnostic role) [ 7 ]. However, there are a few retrospective studies on the therapeutic role of lymphadenectomy in patients with early-stage EOC, with inconsistent results [ 8 9 ]. The recent phase 3 randomized Lymphadenectomy In Ovarian Neoplasms trial reported no survival benefit of lymphadenectomy in patients with advanced EOC with macroscopically complete resection and clinically negative lymph nodes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%